IMPROVING STUDENTSâ READING COMPREHENSION BY USING PEER ASSISTED LEARNING STRATEGIES (PALS) IN EFL CONTEXTS - Sulistami, P; Pahamzah, J; Baratayaomi, W; Syafriza, S (International Journal of Language and Literature, 2018)
This research is aimed to describing the process of teaching reading comprehension and identifying whether Peer Assisted Learning Strategies (PALS) can improve studentsâ reading comprehension at the tenth grade of SMA Negeri 6 Kota Serang. The subject of this research was 30 students in Class X IPS 2. While doing Classroom Action Research (CAR), the researcher was helped by the English teacher as collaborator to observing the research and to know the process of teaching reading comprehension through PALS. The significant improvement of reading comprehension showed from result of pre-test and post-test. The Minimal Mastery Criteria (MMC) score in SMAN 6 Kota Serang in English subject was 75. In the pre-test the average score of studentsâ was 45.6 and there were only 2 students (6.7%) who passed MMC. In the post-test of cycle I, the average score of studentsâ was 69.57 with 12 students (40%) who passed the KKM. The average score of studentsâ post-test II was 83.3 and there were 26 Students (86.6%) who passed MMC. In conclusion, the studentâs reading comprehension was improved and the students were able to comprehend the text through PALS.